CAMPUR KODE DAN ALIH KODE DALAM NOVEL SUPERNOVA 1 KARYA DEWI LESTARI - Susi Purwanti; A. Totok Priyadi; Patriantoro Patriantoro (Universitas Tanjungpura, 2019)
AbstractThis study aims to describe the code mixing and code switching, the causal factors for code mixing and code switching, and describing the plan for implementing sociolinguistic learning in Novel Supernova 1 by Dewi Lestari in College. This research is a qualitative descriptive study. The data source in this study is Novel Supernova 1 by Dewi Lestari with the number of pages 318. Analysis of the data in this study uses the concept of 5W + 1H. The results of this study indicate that there are 125 data which consists of 125 code mixing data and 19 code switching data. The causes of code mixing are factors that limit the use of code, factors that use more popular terms, the speaker and personal factors of the speaker, the factors of residence and time of discussion, as well as the topic or topic of discussion. While the factors that cause code switching in this study are speaker or speaker factors and listener factors or opponents. The plan for implementing learning of code mixing and code switching in Novel Supernova 1 by Dewi Lestari is for college in sociolinguistic courses. Sociolinguistics is taught to students of the Indonesian Language and Literature Education Program semester 3 (three) and has a weight of 2 credits, and is classified into the subject of study program expertise (required). Keywords: Code Mixing, Code Switching, Novel Supernova 1